Analisis Potensi Pengembangan Peternakan Sapi Potong di Kota Tangerang Selatan - Yuniar, P. S.; Widiatmaka, Widiatmaka; Fuah, A. M. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
Urban Agriculture can be described as the growing processing and distribution of food and nonfood plant and tree crops and the raising of livestock, directly for the urban market, both within and on the fringe of urban area. The main aim of this research was to analyze the advisability and the potential beef cattle development in South Tangerang. Datas were obtained from the interview with stakeholders and observation to the livestock locations. Secondary data were obtained from related institutions and litarature.The Analtical Hierarchy Process (AHP) andStrength Weanesses Opportunityand Treaths (SWOT) was used to arrange the strategy of beef cattle development in South Tangerang.The Strengths-Threats strategy were used to optimize the market potentials, humans resources and local goverment suport, reduce the negative effect of environment and limited land resources. The results showed that the application of waste management and biogas technology, enhancement the capacity of farmer cooperatives and the support of goverment in landuse was the important aspect of sustainable to increase farmers income and food security.